Developing composite filament from recycled polypropylene and agriculture waste for fused deposition modeling - Lim, Kar Yap (2023)
Fused Deposition Modelling (FDM) is a widely used and cost-effective additive manufacturing process. However, most of the materials commonly used contribute to environmental waste. Additionally, agricultural waste like corn husks also contributes to environmental waste. Therefore, this research focused on developing a composite filament from recycled polypropylene and corn husk fiber. The corn husk fibers were extracted via the water retting method and further ground into a fine powder. The recycled polypropylene pellet was produced from post-used food containers. The composite filaments were prepared with various fiber content ranging from 0 to 7.5 wt% using a single screw extruder. The filaments with various fiber content were tested for their melt flow index values. Next, the filaments were printed into tensile specimens at different printing parameters and tested for their mechanical properties. The results showed that increasing fiber content reduced the melt flow index, tensile strength, and modulus. However, increasing the printing temperature significantly increased the tensile strength and modulus. It was also found that specimens printed with a filament containing 2.5 wt% fiber content had the highest tensile strength compared to others. Overall, the printed parts using this filament exhibited better mechanical properties compared to those printed with commercial wood filament. However, the inconsistency and incompatibility of the fiber caused some drawbacks in the performance of the composite filament. In conclusion, this study highlights the potential of using recycled materials in FDM and provides insights for optimizing material properties for 3D printing applications.